Producing more rice with less water from irrigated systems (International Water Management Institute, 1998)
This paper reviews the literature on irrigation efficiency and on the potential for increasing the productivity of water in rice-based systems. It stresses the continuing confusion over the concepts of irrigation efficiency and water productivity.